Child Training in Agogo - Anno - Kwakye, V. (Institute of Education, University College of the Gold Coast, Achimota., 1955)
This essay is written about Child Training in Agogo. Place is a village in the Ashanti Akim District on the northern side of Kumasi about forty miles from the latter. A1so, it is eighteen miles away from konongo, a gold mining town on The Accra-Kumasi Railway line. Agogo is situated on the kintampo-Xoforidua range of mountains and thus its climate is the village is more or less surrounded by hil18 and, there is a clear view of it obtainable from the Government Rest house on one of these hills, on the northern side.
Heritage Material
Keywords: Child Training; Parenting; Culture; Agogo